2018
DOI: 10.1111/jmwh.12883
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Ontario Birth Centers into Existing Maternal‐Newborn Services: Health Care Provider Experiences

Abstract: IntroductionIn 2014, 2 freestanding, midwifery‐led birth centers opened in Ontario, Canada. The purpose of this study was to qualitatively investigate the integration of the birth centers into the local, preexisting intrapartum systems from the perspective of health care providers and managerial staff.MethodsFocus groups or interviews were conducted with health care providers (paramedics, midwives, nurses, physicians) and managerial staff who had experienced urgent and/or nonurgent maternal or newborn transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(30 citation statements)
references
References 26 publications
(27 reference statements)
1
29
0
Order By: Relevance
“…Although potential explanations for these positive transfer experiences cannot be concluded from the work we report here, they may be attributable to factors such as health care provider communication, 35,43 the ongoing presence of the midwife through the transfer experience, 35,42 and the manner in which the woman's care was handed over from one professional to another 42 . Previous work by our team demonstrated that health care providers generally described a positive and seamless system for transferring women between birth centers and hospitals 19 . Our findings from this current survey are in alignment with our previous findings from health care providers, suggesting that birth center–hospital transfers are generally working well, but further in‐depth qualitative work is required to better understand specific factors that influence women's transfer experiences in our setting.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Although potential explanations for these positive transfer experiences cannot be concluded from the work we report here, they may be attributable to factors such as health care provider communication, 35,43 the ongoing presence of the midwife through the transfer experience, 35,42 and the manner in which the woman's care was handed over from one professional to another 42 . Previous work by our team demonstrated that health care providers generally described a positive and seamless system for transferring women between birth centers and hospitals 19 . Our findings from this current survey are in alignment with our previous findings from health care providers, suggesting that birth center–hospital transfers are generally working well, but further in‐depth qualitative work is required to better understand specific factors that influence women's transfer experiences in our setting.…”
Section: Discussionmentioning
confidence: 72%
“…We demonstrated that the birth centers are a safe and effective option for women with low‐risk pregnancies seeking a low‐intervention approach to their labor and birth 18 . In addition, we found that the process used to plan and implement the birth centers facilitated integration of the centers into the existing maternal‐newborn health system and increased opportunities for interprofessional collaboration 19 …”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Transfer to a tertiary unit can be stressful, including women feeling they have “lost their dream” 13 and community‐based midwives feeling under‐supported by unit staff 14 . Such problems can be offset by proactive planning of transfer protocols by all relevant personnel 15 . In Angus, where the overseeing obstetrician strongly supports the scheme, a transfer protocol was included from the outset.…”
Section: Discussionmentioning
confidence: 99%
“…14 Such problems can be offset by proactive planning of transfer protocols by all relevant personnel. 15 In Angus, where the overseeing obstetrician strongly supports the scheme, a transfer protocol was included from the outset. The total transfer rate was 22.7% (or 15.3% when excluding women who were ineligible, but who nevertheless requested a home birth (see accompanying paper, this volume).…”
Section: Organizational Structure/work Culturementioning
confidence: 99%